Histiocytosis Presenting as Bilateral Adrenal Masses: A Case Report - Julianne Bullock; Daina Dreimane; Corey Cavannaugh (Case Reports in Oncology, 2024)
Introduction: Adrenal masses are a rare diagnosis in children, with bilateral masses even less common. At present, appearance of the mass on imaging and histology can give important clues to the diagnosis; however, there is significant overlap in 10–30% of cases and it can be difficult to distinguish benign from malignant adrenal masses. As a result, the clinical presentation remains a large part of the diagnostic process, as well as thorough endocrinology evaluation to determine if the tumor is functional versus nonfunctional. Case Presentation: We present a recent case of bilateral adrenal masses in a pediatric patient at our institution, with an unusual diagnosis of histiocytosis. Conclusion: In this case, the diagnosis was unclear, until genetic testing and pathology allowed for expedient diagnosis and targeted therapy for this patient. We hope that presenting this case will increase physician awareness of this condition and expedite diagnosis and treatment in other patients with this rare presentation.